The risk factors of workplace violence among healthcare workers in public hospital - Zainal, Nursyafiqah; Rasdi, Irniza; Muhamad Saliluddin, Suhainizam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Workplace violence become a global concern and perceived as a very serious safety and health hazard especially in healthcare setting. The aim of this study was to determine the prevalence of workplace violence and its associated risk factors among healthcare workers in public hospital. Methods: This was a cross-sectional study which involved 136 randomly selected respondents among doctors and nurses in a public hospital in Kuala Lumpur. Data was gathered through a self-administered questionnaire consisted of two standardized questionnaire; Workplace Violence (WPV) and Job Content Questionnaire (JCQ-27). Results: The response rate was 91%. The prevalence of reported WPV was 71.3% where nurses (73.2%) had slightly higher prevalence than doctors (69.2%). The most common forms of WPV was verbal abuse (70.6%), followed by bullying/mobbing (29.4%), physical violence (11.0%), and sexual harassment (6.6%). The perpetrators were mostly among relatives of patients and visitors followed by the patients. Multiple logistic regression shows that respondents working in Accident and Emergency (A&E) Department was 17 times more likely to report workplace violence than those working in Pediatric Department. Also, for every 1 year younger, respondents were 5 times more likely to experience workplace violence controlling for other factors. Conclusion: The prevalence of workplace violent among respondents were high and most common among young workers, especially nurses and those working in A&E Department. Hence, further assessment should be carried out to reduce the identified risk factors and to find ways of solving this issue.